Pengaruh Pemanfaatan Hybrid Learning terhadap Motivasi dan Prestasi Belajar Mahasiswa di Masa Post Pandemi - Reni Wijaya; Dorris Yadewani; Patria Nagara (Universitas Bumigora, 2023)
Teaching and learning activities in statistics courses are classified as low, this is known from the results of exams held by many students who get low marks. This study aims to determine the effect of using hybrid learning on student motivation and achievement during the post-pandemic period at STMIK Jaya Nusa. This research is quantitative with the census method. The population is students who take statistics courses as many as 70 people. The results of the study show that (1) there is a positive influence between the use of hybrid learning and student learning motivation in the post-pandemic period. (2) There is no positive effect between the use of hybrid learning and student achievement in the post-pandemic period.